Large cell neuroendocrine carcinoma of the larynx: a case report and a review of the classification of this neoplasm. Issue 6 (25th May 2005) - Greene, L; Brundage, W; Cooper, K
Abstract : This report describes a case of large cell neuroendocrine carcinoma (LCNEC) of the larynx. A 74 year old man who presented with otalgia underwent direct laryngoscopy with biopsy, which revealed an invasive poorly differentiated carcinoma. Laryngectomy with bilateral neck dissections revealed invasion of the pre-epiglottic space by the tumour, with metastases to bilateral lymph nodes (AJCC T3N2c). The tumour was characterised by large cells with vesicular chromatin and prominent nucleoli. The cells were arranged in organoid and trabecular patterns with a background of extensive necrosis and numerous mitotic figures. Immunohistochemical and ultrastructural analyses confirmed the neuroendocrine nature of the tumour. Metastatic disease was present in the liver, and the patient died within weeks of surgery. LCNEC carcinoma is a rare tumour of the larynx. Recognition at this site is essential so that proper patient management can be initiated.